2019
DOI: 10.1177/2051415819889552
|View full text |Cite
|
Sign up to set email alerts
|

The decision of targeted, systematic or combined biopsy in a biopsy naïve patient for the diagnosis of prostate cancer, can be made on the basis of multiparametric magnetic resonance imaging

Abstract: Introduction: The current trend to implement multiparametric magnetic resonance imaging (mpMRI)-guided targeted biopsy (TB) as primary biopsy for the diagnosis of suspected prostate cancer and to avoid systematic biopsy (SB) is growing. However, concern remains regarding missing clinically significant (Cs) cancer on the normal mpMRI areas of the prostate. Therefore, we compared the normal and abnormal areas from mpMRI at the same prostate biopsy, using simultaneous SB and TB technique. Methods: A prospective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A change has been made to the target population definition as follows: "Patients with an elevated risk of csPCa (defined as International -In total, 16 cohort studies and the two RCTs mentioned above presented detection rates comparing mpMRI-TB to TRUS-SB. 7,9,11,12,14,16,[22][23][24][31][32][33]40,[42][43][44] Estimates for csPCa showed increased detection favoring mpMRI-TB by 3% (95% CI 0-7, p=0.03).…”
Section: Main Comments Responsesmentioning
confidence: 96%
See 2 more Smart Citations
“…A change has been made to the target population definition as follows: "Patients with an elevated risk of csPCa (defined as International -In total, 16 cohort studies and the two RCTs mentioned above presented detection rates comparing mpMRI-TB to TRUS-SB. 7,9,11,12,14,16,[22][23][24][31][32][33]40,[42][43][44] Estimates for csPCa showed increased detection favoring mpMRI-TB by 3% (95% CI 0-7, p=0.03).…”
Section: Main Comments Responsesmentioning
confidence: 96%
“…Twenty-three trials (all full-text publications) compared mpMRI with a reference standard (n=5, all cohort studies) or with TRUS-SB (n=18: 2 randomized controlled trials [RCTs] and 16 cohort studies) for biopsy-naive men. The certainty of the aggregate study evidence for each comparison showed 14 of the 21 cohort studies to be at either low 6,32,40 or moderate 7,9,11,2,14,16,18,22,25,33,44 risk of bias based on a GRADE approach. 48 One of the RCTs was assessed to be at low risks of bias 20 and the other was assessed at being at unclear risk.…”
Section: Key Evidence For Recommendationmentioning
confidence: 99%
See 1 more Smart Citation